In situ growth of silicon carbide interface enhances the long life and high power of the mulberry-like Si-based anode for lithium-ion batteries. (December 2020) - Weng, Yuehua; Chen, Guorong; Dou, Fei; Zhuang, Xianhuan; Wang, Qiyu; Lu, Mi; Shi, Liyi; Zhang, Dengsong
Highlights: Mulberry-like p-SiOx /SiC@C was created from SiO2 sols. p-SiOx /SiC@C forms by an in situ self-assembly and magnesium reduction approach. In situ growth of SiC interface can prevent the electrolyte from corroding SiOx . The mulberry-like p-SiOx /SiC@C anode exhibits the long life and high power. Abstract: Silicon (Si) attracts attention for its ultra-high theoretical specific capacity (3579 mAh g −1 ) as anodes for lithium-ion batteries (LIB). However, adjusting the contradiction between long life and volume expansion has always been a great challenge for Si-based anodes. In this work, we designed a mulberry-like Si-based anode material (p-SiOx /SiC@C) by an in situ self-assembly and magnesium reduction approach. The most outstanding advantage of this strategy is the formation of silicon carbide (SiC) interlayer between SiOx and carbon coating, which hinders the further reduction of SiOx and realizes controllable specific capacity. The SiC interlayer on the SiOx surface can effectively prevent the electrolyte from penetrating and stabilize the solid electrolyte interphase (SEI) well. As a result, p-SiOx /SiC@C shows stable Li + storage performance and ultra-long cycle stability. Even after 2000 cycles under 2.0 A g −1, p-SiOx /SiC@C still maintains a complete morphology; the capacity retention rate is about 79%; the capacity loss rate is only 0.01% per cycle on average; and it is even more gratifying that the average coulombic efficiency reaches 99.7%. This work opens up a new direction for the practical application of Si-based anode materials. Graphical abstract: Image, graphical abstract